2015
DOI: 10.1242/jcs.172395
|View full text |Cite
|
Sign up to set email alerts
|

A microtubule-independent role of p150glued in secretory cargo concentration at endoplasmic reticulum exit sites

Abstract: Newly synthesized proteins are sorted into COPII-coated transport carriers at the endoplasmic reticulum (ER). Assembly of the COPII coat complex, which occurs at ER exit sites (ERES), is initiated by membrane association and GTP loading of SAR1, followed by the recruitment of the SEC23-SEC24 and SEC13-SEC31 subcomplexes. Both of these two subcomplexes stimulate GTP hydrolysis and coat disassembly. This inherent disassembly capacity of COPII complexes needs to be regulated to allow sufficient time for cargo sor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 31 publications
(61 reference statements)
2
19
1
Order By: Relevance
“…Rather the previously reported active, microtubule-dependent fluctuations of the ER network (the host subtrate of ERES) add onto the domain's microtubule-independent diffusive motion along ER tubules. It is even conceivable that intact microtubules might act against the free motion of ERES on ER tubules since direct interactions via the dynein-motor complex have been reported [12,13].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather the previously reported active, microtubule-dependent fluctuations of the ER network (the host subtrate of ERES) add onto the domain's microtubule-independent diffusive motion along ER tubules. It is even conceivable that intact microtubules might act against the free motion of ERES on ER tubules since direct interactions via the dynein-motor complex have been reported [12,13].…”
Section: Resultsmentioning
confidence: 99%
“…The smooth ER network also hosts distinct export gates for nascent proteins that need to travel along the secretory pathway: After clearance by the quality control machinery [7], properly folded proteins accumulate in stationary membrane domains, called ER exit sites (ERES), where they are packaged into vesicular carrier structures (see [8] for a recent review). The emerging transport intermediates are mostly 50 nm-sized vesicles [9] whose coat machinery is modulated, for example, by cargo proteins [10], sterols [11], and motorassociated factors [12,13] for efficient cargo sorting and subsequent long-range transport.…”
Section: Introductionmentioning
confidence: 99%
“…The following antibodies were used in immunofluorescence (IF) and western blotting (WB) according the manufacturer's instructions at the dilutions indicated. Primary antibodies were: mouse anti-α-actinin (clone EA-53, Sigma-Aldrich; IF, 1:1000; WB, 1:1000), mouse anti-PDI (clone 1D3, Enzo Life Sciences; IF, 1:200), mouse anti-M-cadherin (clone 12-G4, Merck-Millipore; IF, 1:200; WB, 1:500), goat anti-JP2 (Y-15, Santa Cruz Biotechnology; WB, 1:1000), mouse anti-GM130 (clone 35GM130, BD Biosciences; IF, 1:500), rabbit anti-GM130 (Ab52649, Abcam; WB, 1:500), mouse anti-giantin (clone G1/33, Enzo Life Sciences; IF, 1:1000), rabbit anti-giantin (Ab24586, Abcam, IF, 1:2000), rabbit anti-GRASP65 (Ab30315, Abcam; IF, 1:200; WB, 1:500), rabbit anti-p115 (13509-1-AP, Proteintech; IF, 1:200; WB, 1:500), rabbit anti-Sec13 (1:100 for IF; Verissimo et al, 2015), rabbit-anti Lamin B1 (Ab16048, Abcam; WB, 1:2000), mouse anti p62-FITC conjugated (clone 53, BD Biosciences; IF, 1:100), rabbit anti-EAGE (1:2000 for IF; Pepperkok et al, 1993), and mouse anti-VSVG (1:100 for IF; Kreis, 1986). The secondary antibodies used in immunofluorescence were purchased from Thermo Fisher Scientific; horseradish peroxidase (HRP)-conjugated secondary antibodies for western blot analysis were purchased from Sigma-Aldrich.…”
Section: Antibodiesmentioning
confidence: 99%
“…As Ambra1 has been reported to interact with the dynein complex, we thought it likely that Ambra1 may regulate the trafficking of active Src to intracellular autophagic puncta via dynein-dependent processes (Di Bartolomeo et al, 2010), and we found that knockdown of endogenous Dynactin 1 by siRNA inhibited the trafficking of active Src from focal adhesions to autophagosomes. Dynactin 1 is thought to be involved in retrograde trafficking and maturation of trafficking vesicles (Jovasevic et al, 2015;Kedashiro et al, 2015a;Li et al, 2014;Ohbayashi et al, 2012;Verissimo et al, 2015), implying that these may be involved in the redistribution of active Src from focal adhesions to autophagosomal puncta in FAK-deficient cells. We noted that Dynactin 1 knockdown resulted in enlarged late endosomes (not shown), while the number of late endosomes was not altered (not shown), implying that impaired trafficking/maturation of vesicles may be responsible for the block to autophagic targeting of active Src upon Ambra1 and Dynactin 1 knockdown.…”
Section: Control Of Src/fak Spatial Activities Is a Novel Ambra1 Funcmentioning
confidence: 99%